2014
DOI: 10.1007/s11010-014-2151-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Thrombin stimulates VSMC proliferation through an EGFR-dependent pathway: involvement of MMP-2

Abstract: In this study, the role of epidermal growth factor receptor (EGFR), extracellular signal-regulated kinase (ERK1/2), heparin-binding EGF-like growth factor (HB-EGF), general metalloproteinases, matrix metalloproteinases-2 (MMP-2) in mediating the mitogenic action of thrombin in rat vascular smooth muscle cells (VSMC) was investigated. The incubation of rat VSMC with thrombin (1 U/ml) for 5 min resulted in significant (p < 0.001) increase of ERK1/2 phosphorylation by 8.7 ± 0.9-fold, EGFR phosphorylation by 8.5 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
3
25
0
Order By: Relevance
“…Heparinbinding EGF-like growth factor (HB-EGF) is recognized as a ligand that binds to EGFR [31]. HB-EGF is highly expressed in VSMCs and has been shown to stimulate proliferation of VSMCs via autophosphorylation of EGFR [32]. We found that anti-HB-EGF IgG prevented the salusin-β-induced VSMCs proliferation, attenuated the salusin-β-induced EGFR phosphorylation, and abolished the salusin-β-induced phosphorylation of CREB and ERK.…”
Section: Discussionmentioning
confidence: 85%
“…Heparinbinding EGF-like growth factor (HB-EGF) is recognized as a ligand that binds to EGFR [31]. HB-EGF is highly expressed in VSMCs and has been shown to stimulate proliferation of VSMCs via autophosphorylation of EGFR [32]. We found that anti-HB-EGF IgG prevented the salusin-β-induced VSMCs proliferation, attenuated the salusin-β-induced EGFR phosphorylation, and abolished the salusin-β-induced phosphorylation of CREB and ERK.…”
Section: Discussionmentioning
confidence: 85%
“…Over the past two decades there have been studies expanding on GPCR mediated transactivation signalling of PTKR specifically the EGFR [39, 50, 51]. GPCR mediated transactivation dependent signalling also spans out to include activation of the TGFBR1.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that FEOJ blocks FEOJ blocks thrombin-induced migration of VSMCs. Migration of VSMCs is a main step in atherosclerosis (1,2) and thrombin has been reported to induce migration of VSMCs (4,5). To investigate whether FEOJ inhibits thrombin-induced migration of VSMCs, a wound-healing assay was used.…”
Section: Feoj Inhibits Thrombin-induced Phosphorylation Of Akt Inmentioning
confidence: 99%
“…After stimulation with thrombin, VSMCs undergo G1-to-S-phase cell-cycle transition, which is tightly regulated by cyclin D1 and p27KIP1 (2,3). In addition, matrix metalloproteinase-2 (MMP-2) degrades type IV collagen, leading to VSMC migration and the progression of arterial lesions (4,5). A previous study has demonstrated that thrombin stimulates the MMP-2 expression via transcription factor nuclear factor (NF)-κB in chondrosarcoma cells (6).…”
Section: Introductionmentioning
confidence: 99%